Ultrasound-guided ablation for T1N0M0 papillary thyroid carcinoma adjacent and non-adjacent danger triangle area: a retrospective comparative study - Jianchuan Yang; Lingpeng Tang; Yuhan Qiu; Yucheng Lin; Ting Hu; Xiaoying Lin; Songsong Wu (International Journal of Hyperthermia, 2024)
Objectives To compare the safety and efficacy of ultrasound-guided radiofrequency ablation (RFA) in the treatment of T1N0M0 papillary thyroid carcinoma (PTC) with adjacent and non-adjacent danger triangle area (DTA).Materials and methods This retrospective study involved collecting clinical data of all T1N0M0 PTC patients who underwent RFA between January 2018 and December 2020 at the hospital. A total of 211 patients were enrolled in the study (mean age 43.25 ± 12.30 years, male-to-female ratio = 1:3). Among them, 91 had adjacent DTA involvement, while 120 had non-adjacent DTA involvement. Comparisons were made between the two groups patients regarding tumor volume changes, technical success rates, tumor disappearance, disease progression, complications.Results In both groups, the technical success rate was 100%, with a median follow-up period of 30 months. The rates of complete tumor disappearance were 78% (71/91) and 74.2% (89/120) for the adjacent and non-adjacent DTA(p = .517). Disease progression rates were 2.2% (2/91) and 1.7% (2/120) (p > .99), Complication rates were 3.3%(3/91) in the adjacent DTA group and 1.7% (2/120) in the non-adjacent DTA group (p = .654). At 6th month after ablation, the volume reduction rate (VRR) in the non-adjacent DTA group (42.3%) was higher than in the adjacent DTA group (37.3%) (p = .002). However, no significant differences were observed in VRR between the two groups at 1, 3, 12, 18, 24, 30, and 36 months (p > .05).Conclusion In the treatment of T1N0M0 PTC, the complication rates and short-term efficacy of RFA in adjacent to the DTA did not differ from those of non-adjacent DTA.